L’identité brisée. L’image de soi et les marques de subjectivité dans Le Journal de Rutka - Mitura, Magdalena (Studia Romanica Posnaniensia, 2024)
The aim of the article is to reconstruct the self-image by Rutka Laskier, a Jew who died at the age of fourteen in the gas chamber of Auschwitz. It was explicated in the diary she wrote during four months in 1943. This short period of time was enough for her to feel the necessity for finding answers to vital questions due to her impending death. The girl’s lucidity of her tragic situation cracks her identity in statu nascendi and, consequently, disrupts the unity of her textual image. The methodology stays within the framework of the linguistics of enunciation, applied to literary texts. The exploration of the image of Rutka in her writing is done through the traces of subjectivity realised by deictic, affective, evaluative and modal qualifiers.